A Study on the Mandibular Arc of Closure Reproducibility Using the T-Scan III Computerized Occlusal Analysis System. (2015) - Balos, Monica Dora; Soaita, Claudia; Cerghizan, Diana; Popsor, Sorin
Abstract: The reproducibility of the mandibular arc of closure in the articulator is critical in prosthodontics. Since the articulating paper is not a reliable indicator for the occlusal contacts time sequencing, some computerized systems are proposed to be more effective for this purpose. The aim of this study was to assess the reproducibility of the mandibular arc of closure in various types of articulators using the T-Scan III system. The results showed that the first occlusal contact in mouth is close to those observed in the non-arcon articulator. Two main conclusions of the present study are pointed out: (a) both arcon and non-arcon articulators are useful devices to diminish the need for occlusal adjustments in prosthodontics; (b) the T-Scan III computerized occlusal analysis system is not only a powerful diagnostic tool and an accurate way to dynamically measure occlusion in vivo, but also an appropriate device for experimental occlusal studies.